INDIKATOR PEMBELAJARAN AKTIF DALAM KONTEKS PENGIMPLEMENTASIAN PENDEKATAN PEMBELAJARAN AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) - Zul Fahmi (AT-TA'LIM, 2013)
Although fun, active, enjoyable and creative learning as stated by Ministry of Education Affairs (2005) has been implemented on the basis of Education Unit Level Curriculum, there is no clear indicator for the implementation for such an approach.  This article discusses fourteen indicators of active learning based on emergent theories. By understanding the indicator, it is hoped that the teacher are to create conducive classroom athmogphere. Thus, the students actively involve in the learning process, especially to ask questions and convey their ideas.